Governance of the business environment based on food safety disputes: empirical analysis based on the case of “Cordyceps sinensis” - Sun, Jiangjie; Li, Limin; Li, Hui; Liu, Tong; Deng, Jianyi; Zhang, Tingting; Li, Junhao; You, Jinliang; Zhang, Liping (Frontiers in Sustainable Food Systems, 2023)
Introduction The use of the fungus Cordyceps sinensis (CS), which has a long history of use in China for its tonic properties, has sparked controversy based on the risk from high arsenic levels in CS. Methods This study collected all 24 online dispute cases related to CS from the China Legal Documents Network. Excel software was applied to fit the distribution of the sample data and analyze the trend of trial results of CS disputes and the tendency of professional claims trials. The analysis covers the trend of trial results of contract dispute cases involving CS products (CDCCS), and the tendency of the results of CDCCS, using correlation to analyze the factors influencing the results. We analyzed trial tendencies in CDCCS by the methods of complex network analysis (Gephi software) to explore each factor’s effect on the trial outcome of in these claims cases and to predict the trial outcomes of new cases. Simultaneously use KNN to train and predict CS cases. Results The peak number of trial cases was in 2018, and there has been a gradual increase in the rate of losing claims on the claimant. Correlation analysis was used to obtain that the likelihood of the defendant winning a claim is positively correlated with DR, FSS, IDP, and KSP, and negatively correlated with the adoption of JIFDD (3), JIFDD (15), and APL. Gephi software was used to conduct a complex network analysis of the factors influencing the tendency of trial results in CS disputes, showing that noncompliance with FSS, existence of KSP, and submission of IDP evidence by the buyer are the direct factors influencing the seller’s defeat. The seller’s “failure to perform DR” is the key factor in the seller’s defeat in cases. On this basis a probability function is developed to predict a trial win rate of 0.7803 for freshman cases, classifier to predict the remaining four samples and new cases, and get the prediction accuracy is 0.8, 95% CI: (0.2836, 0.9949), and the latter was higher than the former. Discussion It is concluded that the attribute of CS products is a scientific issue, the jurisdiction of CS disputes is confusing and needs to be clarified, and the application of the provisions in judicial trials is cannot adapt to the current environment and needs to be resolved. This study advocates that the government design policy from the top and establish a study on the boundary between administrative and judicial functions to provide a theoretical guarantee to circumvent lazy administration and unscientific law enforcement. The government can provide a legal and regulatory system to improve food quality and regulate management.